Analysis of the organization and development of the technical-material base for tourism and agro-tourism in Vrancea county - Petruţa Antoneta Enache; Manea Drǎghici (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
Vrancea County has an extremely varied relief that is suitable for practicing tourist activities. The paper aims at an analysis of the tourist and agrotourism potential in Vrancea county using the following indicators: the evolution of agrotourism pensions, tourist reception structures, accommodation capacity, etc. The analysis highlighted the fact that the county has vast natural and anthropic resources that are poorly exploited for the development of tourism and agrotourism.
Keywords: L83; 330; tourist and agrotourism potential; tourist activity; accommodation capacity